Oxyphilic thyroid neoplasm in a 10-year-old boy – a familial pattern: case report - Rabska-Pietrzak, Barbara; Maceluch, Jarosław; Harasymczuk, Jerzy; Trejster, Ewa; Warzywoda, Małgorzata; Bręborowicz, Danuta; Niedziela, Marek (Contemporary Oncology/Współczesna Onkologia, 2007)
The oxyphilic tumor is a form of follicular carcinoma, which can occur sporadically or in a familial pattern. Environmental and genetic factors are the underpinnings of the oxyphilic lesion. GRIM-19, a candidate gene located on chromosome 19p13.2 is responsible for mitochondrial metabolism and cell death, and may play the most important role in the development of this tumor. Case report : A 10-year old prepubertal boy was admitted to the hospital because he had a positive family history for oxyphilic thyroid carcinoma. On physical examination he had a goiter (II°) with multiple nodules in both lobes, clinical and hormonal euthyroidism, and a negative serum titer for antithyroid antibodies. The dominant nodule (2.6 × 1.7 × 2.6 cm), solid and hypoechogenic on ultrasound, was localized in the right lobe. A similar but smaller nodule was present in the left lobe. Cytological evaluation of the material from fine-needle aspiration biopsy showed a „suspicious” lesion. Gene expression analysis with RT-PCR techniques revealed a positive result for galectin-3 (an anti-apoptotic protein gene) in the biopsy aspirate. A right lobectomy with the isthmus, along with the removal of the nodule in left lobe, was performed. Histopathological examination showed an oxyphilic adenoma and a macro- and microfollicular colloid goiter. The substitution with L-T4 was initiated. A 3-year follow-up did not show any signs of recurrence. Conclusions : 1. The presence of oxyphilic thyroid carcinoma in an adult should alert the family to perform a screening examination of their biological children in order to detect possible tumor lesions in the pre-invasive stage. 2. In a young child, below 10 years of age, the risk of thyroid neoplasm is high, especially if the family history is positive.